Blended learning: pratical experience in the classroom (Research, Society and Development, 2020)
This article has to analyze how interactive processes involving teacher, student and content were constituted in a discipline, developed in a blended learning model, known as inverted classroom. Such study was carried out in a course of Administration, specifically in the discipline Ethics, Politics and Society. Through participant observation, it was possible to analyze in class how the learning process was constituted, the interaction of the teacher's activity with the students when they solved a problem situation of the discipline. It was possible to identify, comparing with the traditional teaching model, that the student becomes the center of the teaching and learning process and the teacher, many times, is configured as an advisor on the path that the student needs to go.